Hamlet in his modern guises - Welsh, Alexander (Princeton University Press, 2001)
Focusing on Shakespeare's Hamlet as foremost a study of grief, Alexander Welsh offers a powerful analysis of its protagonist as the archetype of the modern hero. For over two centuries writers and critics have viewed Hamlet's persona as a fascinating blend of self-consciousness, guilt, and wit. Yet in order to understand more deeply the modernity of this Shakespearean hero, Welsh first situates Hamlet within the context of family and mourning as it was presented in other revenge tragedies of Shakespeare's time. Revenge, he maintains, appears as a function of mourning rather than an end in its.